Affectivity: new relationship paradigms in the hyperconnected world - F. de Oliveira Sodré , Marcilaine; Cezar Dias , Paulo (Seven Editora, 2023)
Introduction: the family evolved and changed its paradigms, transforming itself into measures that accentuate relationships linked to feelings of affection, happiness and family love, valuing relationships anchored in affection. Initially, it highlights the transformations that have taken place in family concepts and then analyzes the importance of affectivity in family relationships, because the principle of affectivity was instituted to deal with these new standards instituted and supported by the country's legal system. Objectives: to demonstrate some benefits of using technological resources in affective relationships. Methodology: the article adopts the deductive method, a process of information analysis that using logical reasoning and deduction to reach a conclusion about family relationships and affectivity with depth and legal basis, treated by scholars on technological evolution and its implications in family relationships. Considerations: the importance of innovation of familiar concepts in today's world is verified, but that society must be cautious with the relationships built through technological platforms. DOI: 10.56238/pacfdnsv1-037